FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN HIPEREMESIS GRAVIDARUM PADA IBU HAMIL TRIMESTER PERTAMA DI WILAYAH PUSKESMAS TANJUNG PASIR 2020 - Basyariah Lubis; Latifah Hanim; Srimelda Br Bangun; Ronny Ajartha (Fakultas Kesehatan Masyarakat Institut Kesehatan Medistra Lubuk Pakam, 2021)
The incidence of hyperemesis gravidarum in Indonesia ranges from 1% to 3% of all pregnancies. Hyperemesis gravidarum can cause problems in pregnancy such as anemia, while anemia itself can result in shock due to lack of nutritional intake, all of which are eaten and drunk. This study aims to determine the relationship between adaptation and psychological factors with the incidence of hyperemesis gravidarum in pregnant women in the first trimester in the Tanjung Pasir Health Center area. This research is an analytical survey with a cross sectional approach. The study was conducted in the Tanjung Pasir 2020 Public Health Center area from March to August 2020. The population in this study were 108 pregnant women in the first trimester at the Hamidah Clinic and a sample of 52 people. Data were obtained using a questionnaire, data analysis consisted of univariate and bivariate analysis. Bivariate analysis using the Chi Square statistical test at Î± = 5%. The results showed that there was no relationship between adaftation factors (anemia and primigravida) with hyperemesis gravidarum, while psychological factors (unwanted pregnancy, work pressure, income and family harmony) had a relationship with hyperemesis gravidarum. The conclusion of this study is there is a relationship between psychological factors and the incidence of hyperemesis gravidarum in pregnant women in the first trimester in the Tanjung Pasir Puskesmas area. It is suggested that the respondents should increase their knowledge about how to prevent and overcome hyperemesis gravidarum.